A Qualitative Research on the Experience of Education Inspectors in the Process of Fusion and Fission - Hüsnü Ergün; Kazım Çelik (Anı Publishing, 2018)
The supervision sub-system of the Ministry of National Education has been changes by Law no. 6764 dated 02.12.2016. In this study, it is aimed to determine the effects of the education inspectors who work in the provinces after the change in the supervisor subsystem. The research is designed as a research on phenomenology. Content analysis was used to analyze the data. The participants are the seven education inspectors who work in the Western Provinces of Turkey. unstructured interview form was used for data collection. The joining and seperation process, election and appointment process, and assignment process were created from the collected data. The joining and seperation process themes is composed of the sub-themes "Structure regulations" and "using the informal communication process". The election and appointment process themes is composed of the sub-themes "The validity and reliability of the interview is low" and "no appointment for all staff". The assignment process themes is composed of the sub-themes "authority limitation", "assignment outside duty area" and "excess workload". The process that has taken place has caused different negative feelings to be experienced with insufficient morale in the inspectors.